#### Answer

x = 0

#### Work Step by Step

6 (x - 5) =-30
Step 1 : Use the distributive property on the left side of the equation.
6 (x - 5) = 6*x + 6*-5 or 6x -30
Now the equation looks like this.
6x -30 = -30
Step 2: Combine like terms. Check the left side of the equation. There are no like terms. Check the right side. No like terms there either, so go on to Step 3.
Step 3: add 30 to both sides to get the variable term by itself on the right side
6x -30 +30= -30 +30
6x = 0
Step 4 : Divide both sides by 6.
$\frac{6x}{6}$ = $\frac{0}{6}$
x= 0
Step 5: Check. Go back to the original equation
6 (x - 5) = -30
Replace x with 0
-30 = -30
True, so 0 is the correct solution